GAYA BELAJAR BAHASA INGGRIS SISWA DI KELAS IX MTS AL-MUSTAKIM 1 ARANG LIMBUNG - Rika Rika; Nizarrahmadi; Alvina Yolanda; Dewi Ismu Purwaningsih (ADIDAYA : Aplikasi Pendidikan dan Sosial Budaya, 2025)
This research discussed the students’ learning styles in learning English. Learning style is a crucial thing that must be considered. student learning style is an important thing in the teaching and learning process. The aim of this study was to identify students' preferred learning styles. and the most dominates learning style of students in learning English at the ninth grade of MTS Al-Mustaqim 1 Arang Limbung. A qualitative descriptive is used in this research methodology. Students from Madrasah Snawiyah Al-Mustaqim 1, Arang Limbung's ninth grade were the study's subjects. The data collection techniques used are questionnaires, interviews, and documentation. The results showed that the learning styles of students at MTs Al-mustaqim 1 Arang Limbung were very diverse. There are visual, auditory, and kinesthetic learning styles. And the type of visual learners as many as 40 students (57%), auditory learners as many as 19 students (27%) and kinesthetic learners as many as 10 students (14%). As a result, the visual learner type is more dominant than the kinesthetic and auditory.